Difficult Atrial Fibrillation Rate-Control and Digitalis Toxicity in Mitral-Valve Prolapse Patient with Hyperthyroidism - Suryo Ardi Hutomo; Agus Subagjo (Cardiovascular and Cardiometabolic Journal, 2020)
Rate-control is important management in patient with atrial fibrillation. The optimum rate control provides a decrease of symptoms, improves hemodynamics and prevents tachycardia-induced cardiomyopathy. Rate-control could be difficult to achieve because of  patient's comorbidities and special treatment strategy is needed to resolve it. A-46-yo. male, came to ER with palpitation. Holosystolic murmur was heard at apex, radiating to axilla. ECG showed atrial fibrillation, with rapid ventricular response 180 bpm. Echocardiography showed dilated LA and LV, false-normal LV function with EF 59% and anterior mitral-valve prolapse with moderate mitral regurgitation. Acute treatment was administration of digoxin and beta blockers, but ventricular rate wasn’t controlled, until 1.5 mg doses of digoxin was administered. Then patient develops acute digitalis intoxication. After toxicity management, rapid ventricular rate recurs. Patient reevaluation showed hyperthyroidism with low TSH and high T4. Methimazole and propranolol was given and rate-control was achieved shortly after euthyroid state, in 2 months treatment. This patient suffered difficult rate-control despite guidelines-based management. Digitalis intoxication was developed after administration of several therapeutic doses. The diagnosis of hyperthyroidism is central in management of this case. Coexistent of hyperthyroidism and mitral-valve prolapse may be explained by genetic, autoimmune, and thyroid hormone effects in myocardium.